2016
DOI: 10.1249/mss.0000000000000976
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of Exercise Effects on HRQoL in Cancer Survivors after Chemotherapy

Abstract: Beneficial effects of exercise on global QoL and physical function in cancer survivors were mediated by increased cardiorespiratory fitness and subsequent reductions in fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 36 publications
(23 reference statements)
2
26
0
Order By: Relevance
“…The cluster physical fitness and health matches the results from previous quantitative studies that found improved physical fitness to mediate the exercise effects on QoL . In addition, previous studies suggested that psychological variables, such as self‐efficacy and distress, may mediate the exercise effect on QoL .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The cluster physical fitness and health matches the results from previous quantitative studies that found improved physical fitness to mediate the exercise effects on QoL . In addition, previous studies suggested that psychological variables, such as self‐efficacy and distress, may mediate the exercise effect on QoL .…”
Section: Discussionsupporting
confidence: 86%
“…Several reviews and meta-analyses have demonstrated that exercise during or following cancer treatment has beneficial effects on QoL [7][8][9][10][11]. Previous studies indicated that these beneficial effects were mediated by improved physical fitness [12,13] and reduced fatigue [13][14][15]. Improved self-efficacy [12] and reduced distress [12,16] may also mediate the beneficial effects of exercise on QoL.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the exercise-induced benefits on HRQoL were successfully maintained over time in both interventions, despite the return to baseline levels of fatigue. This indicates that besides fatigue, which is found to mediate the exercise effect on HRQoL [ 36 ], other factors also contribute to HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple proposed mechanisms by which physical activity has been linked to physical and mental QoL. First, in prostate cancer exercise intervention studies, fatigue (56,57), cardiorespiratory fitness (57), walking speed (56), upper body strength (56), and lower body functional performance (58) has been identified as possible mediators between exercise intervention and different aspects of QoL. Furthermore, marital status, time since diagnosis, and use of bisphosphonates (58) have been described as moderators.…”
Section: Discussionmentioning
confidence: 99%